Nurses’ Knowledge and Practice in Gastrointestinal Endoscopy: Developing Nursing Guidelines - Sarah Robaiag Alenezi; Suad Dakhilallah O Alatawi; Mujib Rajan Salem Alharbi; Amal Ali Mohammed Alshahrani; Maram Muslam Eid Albalawi; Amira Musallam Almasoudi; Ashwaq Mohammad Ali; Awatif Ghanem Ali Alanazi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Since the first publication on nursing care in 1980, much has been written on nursing care during gastrointestinal endoscopy. However, professional guidelines are mainly focused on the physicians’ practice and training, while little is standardized or written about nursing care in upper and lower GI endoscopy. In the Netherlands, there are no national professional guidelines for nurses offering basic nursing care and post-procedural care for patients undergoing basic GI endoscopy. Most articles in the literature focus on staff training to prevent by passable incidents, and little is said about training on the importance of the non-medical care provided by the endoscopy nurse. An initial step for the development of a guideline is a clear overview and a good understanding of current practice and knowledge. Thus, the central research question of the work presented in this thesis is: What is the current knowledge and practice of endoscopy nurses in the Saudi Arabia in providing nursing care in basic upper and lower GI endoscopy, and what can be concluded about their knowledge and practice, and which areas require improvement?